The Production of Knowledge in Social Work from the Perspective of Gender - Acuña-Pinilla, Wendy Lorena; Ramírez-Patarroyo, María Valentina; Jiménez-Pinzón, Andrea Mireya (Prospectiva. Revista de Trabajo Social e Intervención Social, 2019)
This article presents the results of the research "The production of knowledge in Social Work, from a gender perspective", carried out in the year 2017. This research was based on the documentary review of 157 scientific articles, in four Colombian journals of Social Work during the decade between 2006 and 2016. In addition, four social workers were interviewed. The results identified 16 fields of knowledge production, most of them researched from the Historical-Hermeneutical epistemological approach, that establish a solid relationship between gender and research activity. The conclusion of the article indicates that genderization stigmatizes and subalternize women social workers, as women and their scientific production, in front of their research peers. In addition, there is a strong current of standardization and cultural and political homogenization of knowledge production.